The Effect Of Environmental Value Toward Consumer Behavior on Green Hotel Practice: A Literature Review - Reagan Brian (Jurnal Hospitality dan Pariwisata, 2019)
ABSTRACT As one of the tourism elements hotel have the most impact toward environmental. To cater consumer needs during their stay, hotel consumed huge amount of energy and natural resources and generate waste both liquid and solid. As a tourism amalgam this need to be solved, or at least there is an effort to reduce it. Green hotel pratice comes as one of solution to hotel impact toward environment that has been widely apply. There is much study about green hotel practice that has been done, especially in well develop countries. This study try to provide result study related to consumer behavior toward green hotel practice as a theoretical enrichment for future study. Most of the result shows that environmental awareness value have impact toward consumer responses toward green hotel practice. Consumer have no issues with simplified service in regards of green practice and they also willing to pay premium because of green practice. These result may be differ if the study held in Indonesia, since there are environmental awareness differences and different consumer behavior characteristics. Despite all of the results that may be differ, the hotel could do another environmental awareness act that have least impact on consumer.Keywords: Environmental Awareness Value, Consumer Behavior, Consumer Intention, Consumer Preferences, Green Hotel Practice.